2022
DOI: 10.23887/ijerr.v5i1.45959
|View full text |Cite
|
Sign up to set email alerts
|

Access and Utilization of Online Learning Resources Among Undergraduate Students

Abstract: Online learning resources have made a significant contribution to teaching and learning. It has been felt that many students are underutilizing online learning resources for various reasons. This study aimed to analyze the online learning resources available to undergraduate students, the level of use of online learning resources by undergraduate students, and examine the challenges faced when accessing and using online learning resources. This research is descriptive research with the type of survey research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
0
0
Order By: Relevance
“…Although their acknowledgment was varied, encompassing enhanced study environments and improved relationships, they all underscored the library's crucial function in facilitating effective online resource utilization through the application of modern technologies. The finding aligns with the research conducted by Kofo et al (2022), which highlighted how online learning resources serve the dual purpose of inspiring students to excel academically and facilitating their readiness for future educational undertakings.…”
Section: Theme 2: Technological Supportsupporting
confidence: 86%
“…Although their acknowledgment was varied, encompassing enhanced study environments and improved relationships, they all underscored the library's crucial function in facilitating effective online resource utilization through the application of modern technologies. The finding aligns with the research conducted by Kofo et al (2022), which highlighted how online learning resources serve the dual purpose of inspiring students to excel academically and facilitating their readiness for future educational undertakings.…”
Section: Theme 2: Technological Supportsupporting
confidence: 86%
“…Learning resources are anything that can facilitate a person to gain experience in the form of tools, materials, and even events that can be used as a reference for someone to gain knowledge [1]. The use of learning resources is expected to facilitate teachers and students in learning so that the use of relevant learning resources can support student learning outcomes so that they can achieve the expected goals [2]. The utilization of learning resources is influenced by internal and external (environmental) factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Kofo et al, (2022) on the utilization of online resources in English language learning has shown that many educators have utilized these resources as aids in the learning process. The research results also indicate that the use of online media is effective in supporting conventional learning.…”
Section: Introductionmentioning
confidence: 99%